Opportunities and Challenges in Management Information Systems - Alajmi, Qasim; Sadiq, Ali Safa (Waljat College of Applied Sciences, Muscat, Oman, 2016)
Job creation pivots around producing the needed skills and the talents through education. In Oman, as well as in many Arabic societies, the preferential treatment given to males can be broadly observed. The impact has resulted into numerous empirical discussions on how sociocultural conditions in the Middle East have been affecting the educational pursuits of the female gender. As the number of socio-cultural studies on Arabic women grows, the increasing trend contrarily creates a diminishing proportion for related studies focusing on Arabic men. In view of such discrepancy, the motivation behind this study is to collect data, explore and identify some of the socio-cultural barriers that hinder the studies of young Omani men taking-up Management Information Systems (MIS) at Sultan Qaboos University. There is a limited amount of empirical studies on socio-cultural factors that either influence or impede educational advancement in Oman among men. Thus, this study aims to provide first hand research information and establish data that would offer fresh perspectives while supplementing existing ones as well as the chance to verify the validity of existing available data and share valuable experiences with other information managers. In the conclusion, every young Omani should be aware of the bounds and limitations of MIS. A student’s expectations of the future to pursue a course in MIS should always be kept to a minimum as everyone’s profession lies on electricity and the technology that run the system.